Classification of lava lakes based on their heat and SO2 emission: Implications for their formation and feeding processes - Campion, Robin; Coppola, Diego (Frontiers in Earth Science, 2023)
Lava lakes are a fascinating but somewhat rare form of volcanic activity. Lava lakes are large free surfaces of hot lava that discharge continuously, and almost quietly, heat and volcanic gases into the atmosphere. They are thought to be fed by convection processes that bring hot gas-rich magma to the surface and back downward, after its cooling and outgassing. A lava lake represents a latent threat for the populations living nearby, as it can drain suddenly through fissures and generate dangerously fast lava flows. We present time series of Volcanic Radiative Power (VRP) and SO2 flux measured from satellites (MODIS and OMI, respectively) from several lava lakes on Earth (Erta Ale, Nyiragongo, Kilauea, Nyamuragira, Ambrym, and Villarrica). Based on long-term trends plotted in a simple VRP versus SO2 flux diagram, we propose a new classification of lava lakes in three categories: small lakes, large foam-dominated lakes, and large melt-dominated lakes. Small lakes show a long-term correlation between VRP and SO2 emissions, while large lakes seem to show an anticorrelation between VRP and SO2 emissions. This at-first-glance surprising anticorrelation probably results from the limited heat transport capacity of the gas-rich foam that initially feeds the convection of these lakes. We also show that the formation of three large lava lakes in the last 2 decades at the rift and hotspot volcanoes followed a similar trend of transitioning, in a few months, from foam-dominated to melt-dominated. We deduce that lava lake formation at these volcanoes follows a common sequence of processes that includes the formation of a large shallow magma reservoir and its outgassing through a newly formed pit crater.